Effects of varying oblique angles on flow boiling heat transfer and pressure characteristics in oblique-finned microchannels. (September 2016) - Law, Matthew; Kanargi, Omer Bugra; Lee, Poh-Seng
Highlights: 10° oblique fins provides the least effective heat transfer, followed by 30° and 50°. Heat transfer coefficient increases with oblique angles from 10° to 50°. Increment in oblique angles from 10° to 30° increases pressure drop. Pressure drop is almost negligible when oblique angle is increased from 30° to 50°. Instabilities for the oblique fins are reduced compared to the straight fins. 10° oblique fins has the highest FOM. Interestingly, 30° and 50° have comparable FOM. Abstract: Flow boiling experiments are conducted in oblique-finned microchannels with different oblique angles to investigate its effects on two-phase heat transfer, pressure drop and instabilities. These studies are carried out with FC-72 dielectric fluid at three different oblique angles of 10°, 30° and 50°. Three mass fluxes ranging from 194 kg/m 2  s to 386 kg/m 2  s, and effective heat fluxes from 14.9 W/cm 2 to 70.0 W/cm 2 are tested with high-speed flow visualisations to explore the physical boiling phenomenon in the microchannels. Results show that heat transfer performance increases with oblique angles from 10° to 50° due to the increase in secondary channels which promote flow mixing. This causes an increase in pressure drop from 10° to 30° oblique angles due to the increase in flow separation and flow diversion. Pressure drop, however, is almost negligible when the oblique angles are increased from 30° to 50°. As a result, the 50° oblique-finned microchannels presents an attractive option for further parametric studies.